If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 2) + -1 = -2x Reorder the terms: 2(2 + x) + -1 = -2x (2 * 2 + x * 2) + -1 = -2x (4 + 2x) + -1 = -2x Reorder the terms: 4 + -1 + 2x = -2x Combine like terms: 4 + -1 = 3 3 + 2x = -2x Solving 3 + 2x = -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 3 + 2x + 2x = -2x + 2x Combine like terms: 2x + 2x = 4x 3 + 4x = -2x + 2x Combine like terms: -2x + 2x = 0 3 + 4x = 0 Add '-3' to each side of the equation. 3 + -3 + 4x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 4x = 0 + -3 4x = 0 + -3 Combine like terms: 0 + -3 = -3 4x = -3 Divide each side by '4'. x = -0.75 Simplifying x = -0.75
| x^2+80x-3000=0 | | 9-7(3x+5)=x-2(x+4) | | x^2+80x+3000=0 | | X^2-110x-3000=0 | | 5(6+6)+5x-3= | | 5x+6x-6=5x+8 | | 8x+12=180-(2x+28) | | 7(2c-5)=80 | | -9=3.2+h | | 6.28(r-2)=A | | X^2-110x+3000=0 | | 3sinx=1+cosx | | -3y-27-18-3y=-2(20+y)-5 | | -6x-3=7 | | 8x-6-2x=4 | | 44x+9=7(6x+2)+2x-5 | | 10(2t+5)-8t=56 | | 4(5b-1)-(3b-7)=7-(5b+4) | | 5t=4t-8 | | 7/10=x/7 | | 2(5c+1)-(4c-5)=5-(5c-2) | | cos(4x)=cos(6x) | | 8-(4x+6)=0.5(5-7x) | | (5u+4)(7+u)=0 | | 14x(-3x+5)=3 | | x*2+y=36 | | 14x(3x-5)=82 | | 9w^6+24w^5+16w^4=0 | | 3(3z+4)-4(2z-3)=8 | | 4y^4+18y^3-10y^2=0 | | 7z^2-20z-3=0 | | (3x)2-10= |